Sodium hydroxide mediated alumina nanoparticles from waste aluminum foil sheets – Biological impact and photo-catalytic efficacy on commercial dyes. (2020) - Muthulingam, S.; Greeshma, K.P.; Uthirakumar, A.P.; Thamizselvi, R.
Abstract: Herein, we reported a one-pot facile synthesis of alumina nanoparticles using waste aluminum foil sheet and sodium hydroxide by a simple solution method. The synthesized alumina nanoparticles were examined by UV Visible, X-Ray diffraction studies (XRD), Scanning Electron Microscope (SEM), and Energy Dispersive Analysis by X-rays (EDAX) to determine their size, shape, chemical nature and crystal structure. The average size of the alumina nanoparticles was found to be 50–70 nm. Besides the photocatalytic activity of alumina nanoparticles on two different commercial dyes, viz., MG and MB dyes were evaluated under UV light and naturally available daylight sources. The dye degradation percentages of MG dye under daylight irradiation are ∼17.7% and ∼94.8% under UV light irradiation, ∼14.8% and 90.1% for pure dye and alumina nanoparticles respectively. The percentage of degradation of MB dye in the presence of pure dye, alumina nanoparticles under daylight irradiation, and UV light irradiation are ∼19.6%, ∼92.6%, and ∼6%, 87.2% respectively. These results strongly authenticate the enhanced Photocatalytic activity due to efficient charge separation originating in the alumina nanoparticles. The alumina NPs exhibited an effective antibacterial activity against gram-positive and gram-negative bacteria and also showed an inhibition against human MCF-7 cancer cells, indicating its efficiency in the field of biomedical research.